Aplikasi Sistem Informasi Wisata Religi Di Mojokerto Berbasis Android - Raafisianto, Imron; Sumarno, Sumarno; Azinar, Azmuri Wahyu (STMIK Banjarbaru, 2023)
This research discusses the development of a Religious Tourism Information System Application in Mojokerto based on Android using the Flutter Framework, Multiplatform Advantages, and the Waterfall Method. The Waterfall Method is chosen for its structured and linear framework, ensuring each stage is completed before progressing to the next. The research aims to create an application to facilitate information about religious tourism in Mojokerto. Testing is conducted using the Black Box Testing method to evaluate the functionality of the software. The results of the study indicate that this application supports the tourism experience by promoting cultural and spiritual values. Religious tourism emphasizes religious principles, providing a spiritual and enlightening experience. The importance of promotion in business strategy is reflected in the shift of Instagram's function to a potential social network to support business activities. Information systems play a crucial role in organizing data, facilitating user access. Android provides an open opportunity for developers to create applications according to their preferences. The research conclusion affirms that the Android-based Religious Tourism Information System Application effectively supports the tourism experience in Mojokerto, highlighting the crucial role of promotion, information systems, and the Android platform in business strategy and tourism technology development.Keyword: Tourism Information System Application; Flutter Framework; Waterfall Method; Black Box TestingÂ AbstrakPenelitian ini membahas pengembangan Aplikasi Sistem Informasi Wisata Religi di Mojokerto berbasis Android menggunakan Framework Flutter, Kelebihan Multiplatfrom, dan Metode Waterfall. Metode Waterfall dipilih karena struktur teratur dan linier, memastikan setiap tahap diselesaikan sebelum melanjutkan. Tujuan penelitian adalah menciptakan aplikasi untuk memfasilitasi informasi wisata religi di Mojokerto. Pengujian menggunakan metode Black Box Testing untuk mengevaluasi fungsionalitas software. Hasil penelitian menunjukkan bahwa aplikasi ini mendukung pengalaman wisata dengan mempromosikan nilai-nilai kebudayaan dan spiritualitas. Wisata religi menonjolkan prinsip-prinsip agama, memberikan pengalaman spiritual dan pencerahan rohani. Pentingnya promosi dalam strategi bisnis tercermin dalam pergeseran fungsi Instagram menjadi jejaring sosial potensial untuk mendukung aktivitas bisnis. Sistem informasi memainkan peran utama dalam pengorganisasian data, memudahkan akses pengguna. Android memberikan peluang terbuka bagi pengembang menciptakan aplikasi sesuai keinginan. Kesimpulan penelitian menegaskan bahwa Aplikasi Sistem Informasi Wisata Religi berbasis Android efektif mendukung pengalaman wisata di Mojokerto, menyoroti peran penting promosi, sistem informasi, dan platform Android dalam strategi bisnis dan pengembangan teknologi pariwisata.Â